TASA DE DEFECACIÓN DEL VENADO COLA BLANCA; ODOCOILEUS VIRGINIANUS MEXICANUS; EN CAUTIVIDAD EN PUEBLA; MÉXICO - Pérez Mejía, Silvia; Mandujano, Salvador; Martínez Romero, Luis Enrique (Instituto de Ecología, A.C., 2004)
We present results about the defecation rate of white-tailed deer (Odocoileus virginianus mexicanus) in captivity in the state of Puebla; To obtain this rate for specific deer subspecies is important to estimate the density and to determine hunting rate; The defecation rate was 17 ± 4; but it varies from 8 to 25; In order to reduce possible overexploitation of deer; we suggest to use the maximum estimation of defecation rate to estimate population density.